The Politics of Narrating Everyday Encounters: Negotiating Identity and Belonging Among Berlin’s German-Born Turkish Ausländer - Çalışkan, Gül (Narrative Works, 2015)
This paper is an applied narrative analysis of social encounters and their inherent relationality. The narratives analyzed are those of German-born, Turkish-background Berliners. Although their narratives relate to the specific context of Turkish immigration into Germany, they also shed light on the broader experience of negotiating diasporic identity and belonging, which makes them significant sources for understanding the politics of the Other. The narrative analysis I outline locates the dynamics of discursive messaging within the complexity of human encounters. Narrative is envisaged as one constituent of social interactions within complex processes of othering and the politics of making claims to identity and belonging. This is the struggle of the people who don’t fit and [don’t] belong neatly. (Leyla)1